2021
DOI: 10.1093/cei/uxab032
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and pain in the eye: focus on the ocular surface

Abstract: Most ocular diseases are associated with pain. While pain has been generally considered a mere (deleterious) additional symptom, it is now emerging that it is a key modulator of innate/adaptive immunity. Because the cornea receives the highest nerve density of the entire body, it is an ideal site to demonstrate interactions between pain and the immune response. Indeed, most neuropeptides involved in pain generation are also potent regulators of innate and adaptive leukocyte physiology. On the other hand, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 211 publications
1
1
0
Order By: Relevance
“…Ocular pain is caused by a complex interaction between in ammatory factors and nerves (27). The ocular symptoms we reported in this study are consistent with those reported in other studies.…”
Section: Time Of Last Vaccinationsupporting
confidence: 93%
“…Ocular pain is caused by a complex interaction between in ammatory factors and nerves (27). The ocular symptoms we reported in this study are consistent with those reported in other studies.…”
Section: Time Of Last Vaccinationsupporting
confidence: 93%
“…Corneal epithelial cells are closely related with intraepithelial free nerve endings (FNEs) and the subbasal nerve plexus, which were stained by anti βIII-tubulin. 42 , 43 During corneal wound healing, these nerve fibers, in the form of sensory, sympathetic, and parasympathetic axons, play an important role in controlling epithelial cell regeneration. Sensory nerve endings enhance the adhesion between corneal epithelial cells and improve regenerated epithelial cell maintenance by producing neural-derived growth factors, 6 , 44 – 47 whereas the sympathetic fibers increase and the parasympathetic fibers decrease inflammation.…”
Section: Discussionmentioning
confidence: 99%